SELAYANG PANDANG PENERJEMAHAN - Endro Sutrisno (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2009)
Basically, transferring message from the source to target language, is not just changing the language as there is multidiscipline process in the translation. The complexity performed since the language is multi-system and its variety in communication is never apart from context. Therefore the translation needs not only linguistics theory but also some other theories like socio-linguistics, psycholinguistics, pragmatics, contrastive analysis and cross culture understanding.